Genetic Polymorphisms of Interleukin -1 beta Gene in Association with Multiple Sclerosis in Iraqi Patients - Salman, Ehab D. (Iraqi Journal of Science, 2022)
Interleukin-1 β (IL-1 β) is considered to be one of the most important mediators in the pathogenesis of inflammatory diseases, particularly in neurodegenerative diseases such as multiple sclerosis (MS). MS is a chronic inflammatory disease characterized with demyelination in central nervous system (CNS). There was believe that single nucleotide polymorphisms (SNPs) in IL-1β gene can alter the structure and function of the IL-1β and consequently may have play role in MS disease. In this this study the IL-1β gene polymorphism (rs16944, rs1143634) and their association with MS in Iraqi patients were investigated. Two SNPs including IL-1β-511 (rs16944) in promoter and IL-1B+3962 (rs1143634) in encoding region, were studied using Polymerase Chain Reaction- Sequence Specific Primer (PCR-SSP) technique. The results revealed that IL-1β-511 SNP has three genotypes (CC,CT, TT) with non- significant difference in the SNP genotype and allele frequencies of MS patients compare with control group, it was also noticed that the risk allele was (C) with relative risk (RR=1.55) and higher frequency (60.77%) than T (39.23%) allele in RRMS patients. On other hand the three genotypes (CC,CT, TT) of IL-1B+3962 SNP it seem to have the same picture, that mean there was no significant difference in their frequencies between RRMS patients and control group , and the highest genotype frequency was for (CC) genotype (68.92%) and the lowest frequency was for( TT) genotype (2.88%) in patients, it was also noticed that the risk allele was (C) with odd ratio (2.44) and that the (T) frequencies were (16.98%vs. 33.33%) while (C) frequencies were (83.02 vs. 66.67%) in patients and control group respectively. Concerning with these findings, one can suggest that interleukin-1β gene polymorphisms may not be relevant to susceptibility to MS in Iraqi patients, this is probably due to many reasons such as ethnic diversity, the relevant of haplotype for this gene with other haplotype of cytokine encoding genes and finally the limitation of sample size which play critical role in SNPs studies.